The Impact of Government Behaviors on the Transition Towards Carbon Neutrality in the Construction Industry: A Perspective of the Whole Life Cycle of Buildings - Tang, Daizhong; Gong, Xueyang; Liu, Menglan (Frontiers in Environmental Science, 2022)
Since the early 20th century, the carbon-intensive economy has contributed to a 1 °C rise in the global average temperature, and climate changes caused by carbon emissions have a profound impact on humankind. China currently plans to achieve carbon peak by 2030 and carbon neutrality by 2060. The construction industry accounts for 39% of the total carbon emissions, thus mitigating the carbon emissions in the construction industry (CECI) is crucial to the achievement of the carbon neutrality goal. Government behaviors will significantly affect CECI. Based on a bibliometric analysis with CiteSpace, this study divides government behaviors into government regulations and market-based instruments according to whether compulsory, as beneficiaries in the construction industry must accept the former, but can decide whether to adopt the latter per specific market conditions and development strategies. Furthermore, this study indicates that government behaviors could affect CECI by exerting influence on three stages (material production, construction and operation) in the life cycle of buildings, which is considered the transmission path of government behaviors towards CECI. Given this situation, this study establishes a research framework to analyze the impact of government behaviors on CECI and reviews the impact on each stage. The results revealed that government behaviors present the greatest impact on CECI in the following sectors: 1) the green supply chain management and waste recycling in the material production stage; 2) the green building decisions and the adoption of off-site construction in the construction stage; as well as 3) energy conservation behaviors and green retrofit decisions in the operation stage. Finally, this study discusses the research gaps of prior studies and provides potential directions for future research.